A polymeric bacterial protein activates dendritic cells via TLR4 - Berguer, Paula Mercedes (2006)
The enzyme lumazine synthase from Brucella spp. (BLS) is a highly immunogenic protein that folds as a stable dimer of pentamers. It is possible to insert foreign peptides and proteins at the 10 N terminus of BLS without disrupting its general folding, and these chimeras are very efficient to elicit systemic and oral immunity without adjuvants. In this study, we show that BLS stimulates bone marrow dendritic cells from mice in vitro to up-regulate the levels of costimulatory molecules (CD40, CD80, and CD86) and major histocompatibility class II Ag. Furthermore, the mRNA levels of several chemokines are increased, and proinflammatory cytokine secretion is induced upon exposure to BLS. In vivo, BLS increases the number of dendritic cells and their expression of CD62L in the draining lymph node. All of the observed effects are dependent on TLR4, and clearly independent of LPS contamination. The described characteristics of BLS make this protein an excellent candidate for vaccine development.